2016
DOI: 10.1080/09638237.2016.1207230
|View full text |Cite
|
Sign up to set email alerts
|

Community treatment orders – what are the views of decision makers?

Abstract: When deciding on CTOs, decision makers should pay more attention to the negative consequences that patients may experience. In many cases, decision makers are probably not aware of these coercive factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 17 publications
0
17
0
4
Order By: Relevance
“…Norwegian and international studies show that CTOs are often founded on patients’ lack of insight, to prevent psychotic relapse [ 12 ], which often has a disruptive effect on people’s quality of life and their capacity for independence. A Norwegian study showed that CTO practices vary [ 19 ] and that some RCs only met patients at yearly reviews, knew little about the content of local care services and the impact of CTOs on patients’ everyday lives. Some studies suggest that clinicians’ narrow understanding of ‘lack of insight’ and that a one-sided focus on compliance with medication may impede patients’ recovery process [ 18 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Norwegian and international studies show that CTOs are often founded on patients’ lack of insight, to prevent psychotic relapse [ 12 ], which often has a disruptive effect on people’s quality of life and their capacity for independence. A Norwegian study showed that CTO practices vary [ 19 ] and that some RCs only met patients at yearly reviews, knew little about the content of local care services and the impact of CTOs on patients’ everyday lives. Some studies suggest that clinicians’ narrow understanding of ‘lack of insight’ and that a one-sided focus on compliance with medication may impede patients’ recovery process [ 18 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…ACT targets patients with co-occurring substance abuse and low social functioning who have not remained in care. While some studies describe the implementation of CTOs as a complement to involuntary inpatient care [ 19 , 40 , 41 ], the participants in our study presented the use of CTOs combined with ACT as the least restrictive solution. The Norwegian ACT evaluation did not show a reduction in the number of admissions, but there was a significant reduction in compulsory admissions and total inpatient days.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Community treatment orders indeed now offer the latter public service in some national jurisdictions. However, they do not seem to prioritise an acceptability to patients themselves (Fabris, 2011;Riley et al, 2018).…”
mentioning
confidence: 99%